Optical Observations of Sputtered Au-nanostructures and Characterizations - Sabah Jameel Mezher; Mohammed O. Dawood; Bahjat B. Kadhim (Journal of Techniques)
o develop novel optoelectronic devices, controlling and predetermined absorption is necessary. In the current work, the gold nano-islands were sputtered onto quartz surface substrates using a DC sputtering unit with an optimized chamber. The effects of the sputtering time (10, 15, and 20 seconds) on the characteristics of the golden layers deposited on quartz substrates were studied. Au nanofilms were investigated by XRD (X-ray diffraction), UV-Vis (ultraviolet-visible light) diffractometer, and AFM (atomic force microscopy) techniques. The thicknesses of the three films prepared at different sputtering times (10, 15, and 20 seconds) were calculated using the theoretical deposition formula method. The average layer thickness, and hence the size of the golden crystallites, rose from 6.8 to 13.6 nm when the sputtering period was increased. The X-ray spectra revealed a very distinguish peak at (111), pointing that the gold single crystal has fully oriented along [111] and the gold film has a pure crystalline Fcc structure. When deposition times are lengthened, the color of the resulting films changes from blue to green. Nano-films have seen important changes in their surface shape and roughness. The structural layer of Au's surface is remarkably semi-spherical, giving it the appearance of spherolytic and hummock-like. Analyzing the UV-VIS spectra of the precipitated structures using Tauc's paradigm revealed the optical energy gap (non-zero Eg in the range of 2.36 to 2.38 eV) that is associated with the nanostructure's semiconducting properties. In addition, as the sputtering duration increases from 10 to 20 seconds, the wavelengths at which peak values of the surface plasmon resonance occur shift from 610 to 650 nm, and the widths of the peaks rise. The AFM images of the ultra-thin Au layers showed smooth surfaces whose roughness decreases from 1.82 to 0.673 nm with increasing sputtering time from 10 to 20 nm. Solar cells can take advantage of the higher absorption in the blue spectrum region by using a set of depositing parameters and prescribed thicknesses. In addition, the formation of nano-islands can also be used as nucleation sites (seed layer) to promote the growth of various nanostructures to obtain a good aspect ratio and improve the performance of various optoelectronic devices and gas sensors.